Limits of scientific explanation (II) - Gorazda, Marcin (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2013)
The second part of the text is intended to deal with the anti-naturalistic argument of F.A. Hayek. To present it comprehensively, however, his theory of mind has to be outlined first.According to Hayek, the way in which we perceive the world is entirely grounded in the biological construction of our neural order and thus, from this perspective, he seems to be a naturalist. He excludes any non-natural properties of our cognition like e.g. transcendental free will. However, a closer look at the functioning of our biological apparatus of perception divulges certain inherent and internal restrictions. First of all, we notice that the neural order (biological construction of neurons) is in fact a very complex apparatus of classification and discrimination of sensory impulses. Impulses may come from reality which is outer to the neural order as well as from the inside. The apparatus of classification and discrimination of sensory impulses is not stable, but permanently dynamic. An unstoppable attack of sensations and relevant responses of the system creates new classification rules (neural connections) and demolishes those which have been inactive for a longer time. A system of those rules, existing in a particular time unit, forms a model of reality which imperfectly corresponds to the existing, transcendent reality.The final argument for anti-naturalism which is elucidated in the text is Hayek’s idea of what is explanation and where lie its limits. This idea can be reduced to the following quotation: “…any apparatus of classification must possess a structure of a higher degree of complexity that is possessed by an object which it classifies.” In other words: if our cognitive system is an “apparatus of classification”, and if an explanation means modeling, and if a complete explanation requires the explanation of the apparatus itself, then a complete explanation is not possible at all, as the apparatus, which has a certain level of complexity, cannot upgrade this level in order to explain itself. Hayek’s reasoning is generally approved yet it is emphasized, however, that it rests on very strong assumptions which are identified and named at the end of the text.